The Effectiveness of The Malaria Cadres on Drug Intake Supervision, The Use of Mosquito Net and Environmental Modification on Malaria Sufferers at Malaria Endemic Area of Public Health Center of Waipukang, Lembata District, Nusa Tenggara Timur Province - Kristina, Ragu Harming; Subekti, Sri; Dachlan, Yoes Prijatna; Martini, Santi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Background & objectives: Environmental risk factors, both physical and biological (e.g. ecology of vegetation/plants, forest), equally serve as the risk factors for Anopheles mosquitos breeding. This study was designed to determine a model of spatial mapping for the ecology of vegetation and the potential habitats for the Anopheles mosquitos. Methods: Descriptive epidemiological research was employed to carry out the project, supported with a cross-sectional design. The research took place in Kupang regency, Oesao village, lasting for 2 months from October to November 2014. The ecology of the vegetation and all habitats of the mosquitos in Oesao village were regarded as the population of the research. They were purposively sampled. Results: The vegetation mapping revealed that the land area for rice fields is 169 ha, coconut and banana tress 56.68 ha, maize 67.03 ha, vegetable plants 59.53 ha, forages 21.52 ha, and forests 16.24 ha. The results of the mapping also revealed that the mosquitos breeding sites entail paddy fields, swamps, irrigation channels, and damps. Interpretation & conclution: The ecology of all types of plants mapped serves as potential habitats for the Anopheles mosquitos breeding sites. Plant ecology is quite varied in the Oesao Village, as well as extensive areas of the plant that are closely linked to inadequate growth and development of mosquitoes  and  specific species of Anopheles,  An. vagus and An. annularis. Keywords:  Ecological vegetation mapping; Breeding sites; Malaria mosquitos